2017
DOI: 10.1002/mbo3.450
|View full text |Cite
|
Sign up to set email alerts
|

Illumina sequencing‐based analysis of sediment bacteria community in different trophic status freshwater lakes

Abstract: Sediment bacterial community is the main driving force for nutrient cycling and energy transfer in aquatic ecosystem. A thorough understanding of the community's spatiotemporal variation is critical for us to understand the mechanisms of cycling and transfer. Here, we investigated the sediment bacterial community structures and their relations with environmental factors, using Lake Taihu as a model system to explore the dependence of biodiversity upon trophic level and seasonality. To combat the limitations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 57 publications
4
20
0
Order By: Relevance
“…Our results showed that the bacterial community structure in the nonrhizosphere zones was correlated with NH 4 + , DOC, and OM, similar to the results of other studies in different freshwater ecosystems [6,61]. Notably, SWC and particle size correlated with the bacterial community and network structures in both the P. australis and non-P. australis zones.…”
Section: Links Among Aquatic Macrophytes Local Factors and Bacteriasupporting
confidence: 90%
“…Our results showed that the bacterial community structure in the nonrhizosphere zones was correlated with NH 4 + , DOC, and OM, similar to the results of other studies in different freshwater ecosystems [6,61]. Notably, SWC and particle size correlated with the bacterial community and network structures in both the P. australis and non-P. australis zones.…”
Section: Links Among Aquatic Macrophytes Local Factors and Bacteriasupporting
confidence: 90%
“…Microorganisms include the most diverse and metabolically active taxonomic groups in lake ecosystems and are widely distributed in lake water systems . As microbes are the driving force for nutrient cycling and energy conversion in aquatic ecosystems , microbial physiological function changes affect the form and cycling of nutrient elements in the sediments, and microbes are particularly sensitive and highly susceptible to environmental impacts. Therefore, microorganisms are often used as an ideal indicator for the evolution of lake ecosystems to quantitatively reflect the influence of environmental disturbances on lake ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, bacteria in the sediment also play a critical role in aquatic ecosystems. High-throughput DNA sequencing was used to analyze the sediment bacterial community in Lake Taihu [47]. The data showed that biodiversity is positively correlated with NH 4 + -N in the water and negatively correlated with NO X -N in the sediment.…”
Section: Edna Methods For Eutrophication and Hab Controlmentioning
confidence: 99%